Choosing Competition on Behalf of Someone Else - Fornwagner, Helena; Pompeo, Monika; Serdarevic, Nina (Management Science, 2023)
We extend the existing literature on gender differences in competitive behavior by investigating tournament entry choices when a principal decides for an agent. In a laboratory experiment, we randomly assign subjects the role of either principal or agent. The principal decides whether the agent performs a real-effort task under piece-rate or tournament incentives. When deciding, the principal is informed about the agent’s previous performance, age, and residency. Between treatments, we vary whether the principal knows the agent’s gender. In a baseline treatment, we replicate the standard setting in which subjects decide for themselves whether to compete. Our main findings are, first, that there is no gender gap in tournament entry when principals decide for agents as opposed to the baseline treatment. Second, the gender gap closes because more women are made to compete by principals. Third, whereas there is no gender gap in either of the principal treatments, revealing the agent’s gender is associated with higher overall tournament entry rates. Exploratory analyses of principals’ choice determinants reveal a positive effect of preferences to take risks, competitiveness, and confidence in agents’ performances on making agents compete. In addition, we find no difference in how principals evaluate male and female agents’ performances. Finally, we test the efficiency of principals’ competition choices and show that they lead to fewer payoff-maximizing outcomes than when subjects decide for themselves. Additionally, overall tournament performances and winners’ performances are lower when agents are made to compete, but this effect is not robust to controlling for agents’ previous performances. This paper was accepted by Yan Chen, behavioral economics and decision analysis. Funding: This work was supported by L. Meltzers Høyskolefond; Austrian Science Fund [Grant SFB F63 “Credence Goods, Incentives and Behavior”], and the Department of Economics at the University of Bergen. Also, we are grateful for funding from the Equal Opportunity Coordination Office of the University of Regensburg and its faculty of Business and Economics. Supplemental Material: The supplementary online material and data are available at https://doi.org/10.1287/mnsc.2022.4413 .